2018
DOI: 10.1093/jee/toy009
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin-resistant German Cockroaches Are Less Sensitive to the Insect Repellents DEET and IR3535 than Non-resistant Individuals

Abstract: The German cockroach, Blattella germanica (L.) (Blattodea: Blattellidae), is a serious worldwide pest with a considerable economical and sanitary impact. It is mainly controlled by the application of synthetic insecticides, but repeated use of these substances has promoted the appearance of resistance in cockroach populations throughout the world. The aim of this study was to compare the behavior of deltamethrin-susceptible (CIPEIN colony) and deltamethrin-resistant (JUBA and VGBA colonies) first instar nymphs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Our results provide evidence that broad cross-resistance to insect repellents is present in the pyrethroid-resistant PR mosquitoes. The present results with DEET and IR3535 corroborate those obtained by Mengoni and Algogaray in which pyrethroid-resistant German cockroaches showed less sensitivity to these repellent standards, 23 as well as the report of DEET resistance in a strain of pyrethroid-resistant bed bug (Hemiptera: Cimicidae). 30 Our study also observed significant resistance to both the toxicity and repellency of pyrethrum, transfluthrin, and metofluthrin in the PR strain, similar to that observed for transfluthrin in a selected pyrethroid-resistant strain of Ae.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results provide evidence that broad cross-resistance to insect repellents is present in the pyrethroid-resistant PR mosquitoes. The present results with DEET and IR3535 corroborate those obtained by Mengoni and Algogaray in which pyrethroid-resistant German cockroaches showed less sensitivity to these repellent standards, 23 as well as the report of DEET resistance in a strain of pyrethroid-resistant bed bug (Hemiptera: Cimicidae). 30 Our study also observed significant resistance to both the toxicity and repellency of pyrethrum, transfluthrin, and metofluthrin in the PR strain, similar to that observed for transfluthrin in a selected pyrethroid-resistant strain of Ae.…”
Section: Discussionsupporting
confidence: 92%
“…In related studies, Mengoni and Alzogaray claimed that two deltamethrin‐resistant strains of German cockroach, Blattella germanica (L.) (Blattodea: Blattellidae), had decreased sensitivity to N , N ‐diethyl‐3‐methylbenzamide (DEET) and ethyl 3‐[acetyl(butyl)amino] propanoate (IR3535) . According to their statistical analysis, both strains had reduced responses to IR3535, while only one strain showed about 2‐fold resistance to DEET, even though both strains were highly resistant to deltamethrin (RR > 677).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance rate in the RMKN-BKT and KRSA-BDG was more than 80 and 73 times, respectively. In B. germanica, deltamethrin-resistant cases have been reported previously in several countries such as Malaysia 16 , Singapore 17 , America 12 , Nigeria 18 , South Korea 19 and Argentina 20 . The widespread of deltamethrin-resistant arises presumably due to insecticides' overuse and/or misuse.…”
Section: Discussionmentioning
confidence: 93%
“…Insects with resistant genotypes pay an energetic cost that reduces their fitness compared to susceptible conspecifics. Hemiptera, Diptera, Coleoptera, and Lepidoptera have all been observed with this trait ( Kliot and Ghanim, 2012 ; Mengoni and Alzogaray, 2018 ; Castellanos et al, 2019 ). Compared to other resistant strains of German cockroach, certain pyrethrin- and allethrin-resistant cockroaches have an irregular pattern of development among the nymphs and a lower total fecundity ( Zhang and Yang, 2019 ).…”
Section: Blattodeamentioning
confidence: 99%